Studi Karakteristik Siswi Penerima Program Tablet Tambah Darah sebagai Antisipasi Stunting: Studi Karakteristik Siswi Penerima Program Tablet Tambah Darah sebagai Upaya Pencegahan Anemia pada Remaja - Guntari Prasetya; Ali Khomsan; Hadi Riyadi; Faisal Anwar (Universitas Airlangga, 2022)
Background: Efforts to accelerate stunting reduction involve specific and sensitive nutrition interventions. School adolescent girls are the target group in reducing stunting through anemia prevention. Iron folic acid (IFA) supplementation program is the specific nutrition intervention to prevent anemia in adolescent girls. Objectives: This research aims to study the characteristics of students who received the IFA supplementation program. Methods: Research design was a cross sectional that involved 123 students from 12 public high schools in Cianjur District, West Java Province. Student’s characteristics consist of knowledge on anemia and their adherence on IFA supplementation program. Data collection is carried out by self-administering questionnaires monitored by enumerator. Data is performed by using mean ± SD and n (%). Results: Student’s knowledge on anemia mostly (61.8%) were categorized as low, as 30.9% were moderate, and only 7.3% were high. Students (44.7%) knew how to detect anemia is by measuring blood hemoglobin levels. As of 59.3% and 51.2% students knew the main causes of anemia are inadequate iron intake and blood loss during menstruation. Approximately 60-80% students recognized the common symptoms and sign of anemia. Most students (76.8%) have received IFA on a weekly basis and 41.2% students acknowledge their adherence in the IFA consumption with aim to prevent anemia (85.1%), the rest 23.4% and 14.9% due to the advice by the teachers and health officers. Students who have no adherence were due to their fear on the side effects, the tablet taste, forgetfulness, and feeling healthy. Conclusions: Iron folic acid supplementation program have been conducted and well targeted, however, student’s understanding on the objectives, benefit, and their adherence is needed to be gained.